(untitled) (Journal of actual problems of jurisprudence, 2024)
The article considers an integral part of society as an institute of administrative law arising from social relations in ordinary life. The aspects of the elements of administrative justice are considered and studied. Necessary facts affecting the emergence of this institute of law are established. Procedural peculiarities of consideration of administrative case, relations that are the subject of administrative case are categorized. The concepts of administrative appeal and the concept of administrative claim are studied in detail and their differences are stipulated. The peculiarities of the order of consideration of classification types of complaints are stated. This study aims to assess the effectiveness of administrative appeal as a mechanism of legal protection by analyzing normative legal acts, judicial practice and international standards and practices. This study takes a comprehensive approach, including analysis of legislation and judicial practice, as well as comparative legal analysis between countries. This work is important in order to better understand the role of administrative appeal in our legal system. In addition, the practical significance of the work lies in the use of its conclusions to improve legislation and optimize administrative procedures. The contribution of the institute of administrative appeal in ensuring human rights and freedoms and its difference from administrative lawsuit is determined. It is studied that administrative appeal as an institute of law is the only special system, which realizes a special function, inseparable in social relations, relations between the state and the people. Keywords: administrative law, complaint, general and special complaint, administrative action